Analysis of the Use of Podcast Learning Media in Indonesian Language Learning on Students' Speaking and Listening Abilities - Hamdayani, Ria; Sapitri, Maya (International Journal of Curriculum Development, Teaching and Learning Innovation, 2025)
This research explores the use of podcast learning media in enhancing students' speaking and listening skills in Indonesian language learning. Podcasts, offering accessible and authentic content, have emerged as a flexible tool for language acquisition, providing students with opportunities to practice listening comprehension and speaking outside traditional classroom settings. The study investigates the effectiveness of podcasts in improving these language skills, focusing on a group of students engaged in podcast-based learning activities. Findings indicate that podcasts contribute positively to students' language development, particularly in listening and speaking proficiency, although challenges such as technological limitations, content accessibility, and lack of interactive speaking practice were identified. The study highlights the need for careful integration of podcasts into the curriculum, with a focus on addressing technological barriers and providing complementary interactive activities. The research contributes to the understanding of podcast-based language learning, offering insights into its potential benefits and limitations. Further research is recommended to explore the long-term effects, integration with other teaching methods, and its impact on additional language skills such as reading and writing.